Menyoal Kurikulum 2013 dalam Sistem Pembelajaran Berbasis Teknologi Informasi Guna Mengembangkan Soft Skills dan Pendidikan Karakter Anak - Rahmad Hidayat (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2021)
To review the problem above, this article focuses on three problems; 1) what is the form of implementing Curriculum 2013 in an information technology-based learning system, 2) what are the factors that cause the neglect of the quality of soft skills and the value of children's character in this learning model, and 3) what are the implications? To examine the research problem above, the author will use Paulo Freire’s theory of "Critical Education" to understand the pattern of teacher-student relationships in his learning model. The method used is a literature study by collecting sources from books, texts, or documents that discuss this issue. It can be concluded that the findings in this article are as follows; 1) Curriculum 2013 can still not be applied optimally in ITE-based learning, because soft skills are negated. 2) The ITE-based learning model still places students as objects and teachers as subjects, which means that in Curriculum 2013, these two relationships will be aligned. 3) The above model has implications for the decline in student character values and neglected aspects of soft skills.